Characterisation of quorum sensing and quorum quenching soil bacteria isolated from Malaysian tropical montane forest / Chong Teik Min - Chong, Teik Min (2012)
Quorum sensing (QS) describes bacterial cell density dependent signaling mechanisms through autoinducers that are involved in mediation of bioluminescence, biofilm development, antibiotic production and virulence factor expressions. Attenuation of quorum sensing signals termed as quorum quenching (QQ) have been identified in a range of living organisms, including bacteria and eukaryotes. The production and degradation of QS compound N-acyl homoserine lactones (AHL) by bacteria isolated from Malaysian montane forest soil were assessed in this study. Phylogenetic analysis indicated that these isolates were distinct members of genera of Arthrobacter, Bacillus and Pseudomonas. Biosensor screening and liquid chromatography mass spectrometry analysis have revealed the production of N-dodecanoyl-L-homoserine lactone (C12-HSL) by Pseudomonas frederiksbergensis (isolate BT9). Strong QQ activity with broad substrate specificity against various AHLs has been detected among Arthrobacter, Bacillus and Pseudomonas isolates using whole-cell AHL inactivation assay and rapid resolution liquid chromatography analysis (RRLC). In addition, degradation of p-coumaroyl-homoserine lactone by Arthrobacter and Pseudomonas spp. was documented first in this study. Further studies involving whole genome sequencing of these isolates for the purpose of assessing regulation of QS and QQ genes is currently being carried out.